ANALISIS MANTRA PENGOBATAN MASYARAKAT DI KMPUNG AIR KELAT KABUPATEN LINGGA PROVINSI KEPULAUAN RIAU - Wisang, Paskalia; Ahada Wahyusari; Zaitun, Zaitun; Isnaini Leo Shanty; Suhardi, Suhardi; Asri Lolita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the structure and function of healing mantras developed in the community of Kampung Air Kelat, Lingga Regency, Riau Islands Province. The selection of research objects was based on the community's strong belief in traditional healing practices performed by shamans, as well as the uniqueness of the language and cultural values contained in the healing mantras used. This study used a qualitative approach with descriptive methods. The research subjects were traditional healers in Kampung Air Kelat, while the research object was the healing mantras used in healing practices. Data collection techniques included observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data classification, data interpretation, and data inference. The results of the study show that the structure of the healing mantras of the Air Kelat Village community refers to Suwardi Endraswara's theory, which consists of an opening, content, and closing. The function of healing mantras is not only as a means of praying to God for a smooth healing process, but also as a medium for traditional healing, preservation of religious values and local wisdom, and a reinforcement of social solidarity in the community. This research is expected to enrich the study of oral literature, particularly healing mantras, and contribute to the documentation and preservation of Malay oral cultural heritage in the archipelago.